Does Consciousness Cause Behavior? - Pockett, Susan; Banks, William P.; Gallagher, Shaun (Cambridge, MA MIT Press, 2006)
Our intuition tells us that we, our conscious selves, cause our own voluntary acts. Yet scientists have long questioned this; Thomas Huxley, for example, in 1874 compared mental events to a steam whistle that contributes nothing to the work of a locomotive. New experimental evidence (most notable, work by Benjamin Libet and Daniel Wegner) has brought the causal status of human behavior back to the forefront of intellectual discussion. This multidisciplinary collection advances the debate, approaching the question from a variety of perspectives.The contributors begin by examining recent research in neuroscience that suggests that consciousness does not cause behavior, offering the outline of an empirically based model that shows how the brain causes behavior and where consciousness might fit in. Other contributors address the philosophical presuppositions that may have informed the empirical studies, raising questions about what can be legitimately concluded about the existence of free will from Libet's and Wegner's experimental results. Others examine the effect recent psychological and neuroscientific research could have on legal, social, and moral judgments of responsibility and blame--in situations including a Clockwork Orange-like scenario of behavior correction.Contributors:William P. Banks, Timothy Bayne, Sarah-Jayne Blakemore, Suparna Choudhury, Walter J. Freeman, Shaun Gallagher, Susan Hurley, Marc Jeannerod, Leonard V. Kaplan, Hakwan Lau, Sabine Maasen, Bertram F. Malle, Alfred R. Mele, Elisabeth Pacherie, Richard Passingham, Susan Pockett, Wolfgang Prinz, Peter W. Ross
Keywords: Philosophy